Reference measurement procedures for Alzheimer's disease cerebrospinal fluid biomarkers: definitions and approaches with focus on amyloid β42. (August 2012) - Mattsson, Niklas; Zegers, Ingrid; Andreasson, Ulf; Bjerke, Maria; Blankenstein, Marinus A; Bowser, Robert; Carrillo, Maria C; Gobom, Johan; Heath, Theresa; Jenkins, Rand; Jeromin, Andreas; Kaplow, June; et al.
Cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease (AD) are increasingly used in clinical settings, research and drug trials. However, their broad-scale use on different technology platforms is hampered by the lack of standardization at the level of sample handling, determination of concentrations of analytes and the absence of well-defined performance criteria for in vitro diagnostic or companion diagnostic assays, which influences the apparent concentration of the analytes measured and the subsequent interpretation of the data. There is a need for harmonization of CSF AD biomarker assays that can reliably, across centers, quantitate CSF biomarkers with high analytical precision, selectivity and stability over long time periods. In this position paper, we discuss reference procedures for the measurement of CSF AD biomarkers, especially amyloid β42 and tau. We describe possible technical approaches, focusing on a selected reaction monitoring mass spectrometry assay as a candidate reference method for quantification of CSF amyloid β42.